Development of Strategy and Sustainability of Bank Syariah Mandiri Management in The Face of Covid-19 Pandemic - Renny Oktafia; Diah Krisnaningsih; Tika Widiastuti (IQTISHODUNA: Jurnal Ekonomi Islam, 2021)
Bank Syariah Mandiri is a sharia-based financial industry that serves as advancing economic growth in Indonesia. The Covid-19 pandemic has greatly affected the community, including the sharia banking industry sector. The purpose of this research is to answer the problem formulation regarding the implementation of Bank Syariah Mandiri management strategies to survive the COVID-19 pandemic by undertaking several risk mitigation measures, namely (1) restructuring customers applying for financing; (2) perform backups; (3) creating a customer base; (4) create a webinar program as a gathering and outreach to customers; (5) teller and customer service employees are required to be able to market and have their customers. The number of assets, financing, deposits and profits of Bank Syariah Mandiri during the pandemic experienced the best increase during its establishment. The condition of the development of Bank Syariah Mandiri is good because since 2015 it has begun to improve the work system to modern technology. Also, Bank Syariah Mandiri is developing well and has collaborated with several agencies such as BUMN, civil servants, hospitals, private employees, the Ministry of Religion, and the Ministry of Finance.